Food safety and quality systems in developing countries. - Gordon, Andre (Academic Press is an imprint of Elsevier, 2017)
This book provides information related to pressing global problems aligning with food safety, food security, governance, environment, and sustainable development in an age of globalization, covering the application of science, the transformation of production systems, regulatory underpinnings, and trade and marketing considerations.